Polysulfide-Permanganate Flow Battery Using Abundant Active Materials. Issue 7 (9th July 2021) - Yang, Zhiwei; Gerhardt, Michael R.; Fortin, Michael; Shovlin, Christopher; Weber, Adam Z.; Perry, Mike L.; Darling, Robert M.; Saraidaridis, James D.
Abstract : A new flow battery is presented using the abundant and inexpensive active material pairs permanganate/manganate and disulfide/tetrasulfide. A wetted material set is identified for compatibility with the strongly oxidizing manganese couple at ambient and elevated temperatures. Both solutions allow high active material solubility, with cells tested at theoretical energy densities up to 43 Wh l −1 for the ∼1.2 V cell. Full cells built with nickel foam electrodes and sodium-exchanged Nafion 115 membranes deliver a baseline area-specific resistance of 2.7 Ω-cm 2 . Incorporation of high-surface-area cobalt-coated carbon paper and high-surface-area stainless steel mesh electrodes, and an expanded Nafion 115 membrane delivers cells with 44% lower resistance at 1.6 Ω-cm 2 . All cells show performance decay over the course of cycling. The Co-decorated carbon paper electrodes provide significant kinetic improvements, shifting electrode performance from non-linear with Ni-foam to linear with a volume-normalized exchange current density value of 3.2 A cm −3 . The expanded membrane provides increased conductivity over the 13 mS cm −1 conductivity observed in as-received, sodium-exchanged Nafion 115. Although boiled membranes provide improved conductivity, it is at the cost of decreased Coulombic efficiency and poorer manufacturability. Full cell models suggest that similar cell resistances (1.7 Ω-cm 2 ) should be feasible with as-received Nafion 115 and advanced electrodes.